Prognostic value of circulating tumour DNA during post‐radiotherapy surveillance in locally advanced esophageal squamous cell carcinoma. Issue 11 (27th November 2022) - Wang, Xin; Yu, Nuo; Cheng, Guowei; Zhang, Tao; Wang, Jianyang; Deng, Lei; Li, Jiao; Zhao, Xiaotian; Xu, Yang; Yang, Peng; Bai, Na; Li, Yin; et al.
Abstract: Background: The potential of circulating tumour DNA (ctDNA) as a reliable biomarker for relapse/metastasis early detection and prognosis in esophageal squamous cell carcinoma (ESCC) after radiotherapy/chemoradiotherapy (RT/CRT) initiation requires comprehensive investigation. Methods: Treatment‐naive locally advanced ESCC patients with available baseline plasma samples were prospectively enrolled from November 2018 to January 2020. RT/CRT was delivered with a simultaneous integrated boost of radiation dose. Serial plasma samples were collected at baseline (T0 ), week 4 of RT/CRT (T1 ), 1‐3 (T2 ) and 3‐6 months post‐RT/CRT (T3 ). ctDNA was analysed using next‐generation sequencing of 474 cancer‐relevant genes. Results: A total of 128 plasma samples from 40 eligible patients were analysed (median age: 64 [range: 40‐78], 88% males, 95% stage III/IV), and the median follow‐up time was 20.6 months (range: 12.2‐33.3). During the post‐RT/CRT surveillance including 36 patients, radiological progression was observed in 16 patients, and 69% (11/16) had detectable post‐RT/CRT ctDNA prior to radiological progression, with a median lead time of 4.4 months compared with radiological imaging. ctDNA positivity at T1 (hazard ratio, HR: 3.60, 95% confidence interval, CI: 1.30‐10.01) or T2 (HR: 5.45, 95% CI: 1.72‐17.26) indicated inferior progression‐free survival (PFS). ctDNA clearance between T0 ‐T1 (HR: 0.31, 95% CI: 0.08‐1.13) or T0 ‐T2 (HR: 0.11; 95% CI: 0.02‐0.61) was associated with relatively favourable PFS. Similar results were obtained when focusing on patients without esophagectomy after RT/CRT. Notably, detectable ctDNA at T1 was a potential indicator of high local recurrence risks (HR: 4.43, 95% CI: 1.31‐15.04). Conclusions: ctDNA was identified as a robust biomarker for early detection of disease progression and post‐RT/CRT prognosis stratification in ESCC. Detectable ctDNA at week 4 of RT/CRT might indicate higher local recurrence risks, implying the potential clinical utility of ctDNA tests in guiding post‐RT/CRT treatments for locoregional control in ESCC. Abstract :